2023
DOI: 10.18517/ijaseit.13.2.18252
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Alzheimer’s Disease Using Novel Dual Decomposition Technique and Machine Learning Algorithms from EEG Signals

Abstract: Alzheimer's disease (AD) is one of the neurodegenerative disorders. The rate of AD prevalence is rapidly increasing worldwide. The existing clinical invasive methods and neuro-imaging techniques to detect AD are time-consuming, subjective, and expensive. To overcome these issues, we proposed a new automatic framework for detecting AD at an early stage based on the dual decomposition method. Initially, EEG signals of mild cognitive impairment (MCI), AD, and normal control (NC) patients are divided into five sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…A total of 40 articles (Table 3 , Ref. [ 20 , 25 , 26 , 27 , 28 , 30 , 31 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]) published between 2000 and 2023 using entropy measures were included (Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 40 articles (Table 3 , Ref. [ 20 , 25 , 26 , 27 , 28 , 30 , 31 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]) published between 2000 and 2023 using entropy measures were included (Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Machine learning-based approaches have been successfully applied to discriminate AD patients from HC, MCI subjects, and individuals with Subjective Cognitive Complaint (SCC) (Table 4 , Ref. [ 20 , 25 , 26 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 58 , 59 , 61 , 62 , 63 , 64 ]). These studies have also found significantly lower entropy values in AD than in HC and a high discriminative capability [ 20 , 25 , 36 , 37 , 40 , 58 , 59 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Learning from historical data, artificial neural networks (ANNs) may produce intricate patterns and improve prediction accuracy (Cepowski et al, 2021;Ihsan et al, 2023). Since they can generalize from trained data, they are perfect for scenarios involving large, diverse datasets and enable better operational planning, prediction, and management for a large number of fields such as education (Haque et al, 2024;Yaqin et al, 2021), society and human (Capote-Leiva et al, 2022;Kannan et al, 2023), energy and fuels (Le et al, 2023;Notton et al, 2019;Taghavifar and Perera, 2023), economy (Moonlight et al, 2023;Suvon et al, 2023), medicine (Puri et al, 2023;Yeo et al, 2023), manufacturing and industry (Cong My et al, 2023;Radonjić et al, 2020;Rosiani et al, 2023), environment (Biswas et al, 2024;Zarra et al, 2019), food and agriculture (Chaivivatrakul et al, 2022;Swasono et al, 2022), transportation (Abramowski, 2008;H. P. Nguyen et al, 2024a;V.…”
Section: Artificial Neural Networkmentioning
confidence: 99%